Síntese e aplicação do óxido misto de zinco e estanho (IV) na degradação fotocatalítica do cloridrato de ciprofloxacino - Pompeu, Sharon Ditzel (2020)
Contamination of the environment by organic compounds of anthropogenic origin has led to severe ecological imbalances. This project aims to develop methodologies using a low-cost energy source, artificial or solar light, associated with the use of compounds that can act as catalysts that lead to the degradation of these contaminants. In the experiment two zinc oxides doped with tin in two different molar proportions Zn: Sn, 20: 1 (Cat1) and 2: 1 (Cat2) were synthesized by the co-precipitation method. The prepared catalysts were applied in the photocatalytic degradation of the antibiotic ciprofloxacin hydrochloride (CIP) in aqueous solution, using an experimental design 22 to verify the influence of the parameters catalyst concentration (mg L-1) and Zn: Sn molar ratio of catalyst in the degradation process, with the CIP absorbance reduction percentage (% RedAbs) as the response parameter. Due to the results obtained in the experimental design, the condition that showed the best efficiency in degradation was the Cat2 catalyst, in the concentration of 25 mg L-1, which presented %RedAbs of 57%. The characterization tests proved the doping efficiency making this catalyst more efficient. Still as a comparative end between ZnO, synthesized and commercial, both presented very similar results even though they had different origins. This fact proves the presence of the final product in both products. The results obtained in this work allow us to conclude that the method developed for the degradation of the CIP antibiotic in aqueous solution, with the use of ZnO / SnO2 ultraviolet irradiation proved to be efficient.